The Use of Monopoly as a Learning Media to Teach Students' Reading Skills - Daradjah, Zakiah Muftie; Munjiah, Ma'rifatul; Huda, Miftahul (STIQ Amuntai, 2025)
The learning of reading skills is one of the important aspects in mastering the Arabic language. However, the lack of motivation and student engagement in the learning process often becomes an obstacle in achieving learning goals. Therefore, innovation in the use of learning media is needed to enhance student motivation and interactivity. This study aims to 1) determine the use of Monopoly media in teaching reading skills to students at MTs Islamiyah Malang and 2) identify the supporting and inhibiting factors in the use of Monopoly media in this learning process. The research employs a qualitative descriptive approach using observation, interviews, and documentation methods to collect data. The research subjects are teachers and students of MTs Islamiyah Malang who are directly involved in the learning process. The results indicate that the use of monopoly media in teaching reading skills has a positive impact on students' motivation and engagement. This media makes learning more interesting and interactive, thereby motivating students to actively participate in reading Arabic texts. Additionally, teachers find the structured gameplay helpful in delivering material more enjoyably. The supporting factors for using monopoly media in teaching reading skills to MTs students are 1) high student interest in game-based learning media, 2) attractive learning material design, and 3) available learning facilities at school. Meanwhile, the inhibiting factors include 1) limited instructional time, 2) differences in students' abilities, and 3) technical constraints.